Open access to research artifacts: Implementing the next generation data management plan. Issue 1 (18th October 2019) - Stodden, Victoria; Ferrini, Vicki; Gabanyi, Margaret; Lehnert, Kerstin; Morton, John; Berman, Helen
ABSTRACT: We describe a new vision for a Data Management Plan (DMP) that incorporates controlled vocabularies and semantic descriptions of the scholarly objects to be produced by the proposed project. We implement this vision in an open‐source web‐based DMP tool, called ezDMP, atezdmp.org . The integrated use of structured information in ezDMP permits several important goals. First, with minimal additional effort, researchers can create DMPs with more complete information about the scholarly objects to be produced. Second, research funders can productively query this structured information to learn about repository use and other patterns of scholarly objects creation. Finally, ezDMP puts a structure in place that can support the integration of information about digital scholars objects, in an organized and systematic way, into research data management environments.